Rekonstruksi Perlindungan Hukum Korban Kekerasan Seksual di Lingkungan Perguruan Tinggi: Analisis Ketimpangan Relasi Kuasa dan Paradoks Locker Room Talk di Era Digital - Tengku Chintya Khairunnisa; Muhammad Hadzami Alma’arif (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Electronic-Based Sexual Violence (EBSV) in higher education has continued to increase alongside the expansion of digital interactions and the normalization of locker room talk, which reinforces unequal power relations. This study aims to analyze the barriers to legal protection for victims arising from unequal power relations and to formulate a reconstructed model of legal protection that integrates institutional strengthening, digital evidence mechanisms and legal culture reform. The research employs a normative juridical method using statutory and conceptual approaches grounded in feminist legal theory. The findings reveal that unequal power relations and the culture of locker room talk undermine the effective implementation of Minister of Education, Culture, Research and Technology Regulation No. 30 of 2021 and Law No. 12 of 2022 on Sexual Violence Crimes. The novelty of this study lies in the formulation of an integrated legal protection model that extends beyond regulatory reinforcement by combining the institutional independence of the Sexual Violence Prevention and Response Task Force (Satgas PPKS), enhanced digital forensic capacity, optimization of electronic evidence and gender-responsive legal culture reform into a comprehensive victim protection framework within higher education institutions. This model is expected to strengthen the effectiveness of legal protection for victims of Electronic-Based Sexual Violence in higher education.